If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4y = -37 Solving 9x + -4y = -37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 9x + -4y + 4y = -37 + 4y Combine like terms: -4y + 4y = 0 9x + 0 = -37 + 4y 9x = -37 + 4y Divide each side by '9'. x = -4.111111111 + 0.4444444444y Simplifying x = -4.111111111 + 0.4444444444y
| x^2+4(x-3)=0 | | 3(x^2+2x)=9 | | 3x+(x-2)+(2x-1)=18 | | 1-5x+6x^2=0 | | 5-3x-2x^2=0 | | -5y+6=-4(2y+3) | | x+3=2x^2 | | y=8-12+2y | | 5x+20x=1320 | | 5x-20x=1320 | | -(a-5)+7=-(8+3a) | | -4(1+2n)=-2(n-1) | | 90=10(x+16) | | x+(x-2)= | | 17x=-12 | | 5(v-7)=-39+3v | | 6(x+1)=-5x-5 | | 35=10b+50 | | 2x+4(2x+7)=3(2x+4) | | -(3+2x)=17 | | 4b^2=9 | | 6-(-6b-3)=-3b-27 | | -32-5x=2(4x-6)-7 | | a-0.66667a=8 | | -3(2z-5)=-2z-3z+21 | | 6-x=8-2x | | (X-5)1.5=8 | | a-0.75a=6 | | x(x-12)=-35 | | 6+0.75a=a | | 2(x-6)-6(x-2)=x+5-(x-11) | | -2x+13=10-2x |